2017
DOI: 10.1128/jb.00357-17
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the Functionally Important Domain and Amino Acid Residues in Mycobacterium tuberculosis Integration Host Factor for Genome Stability, DNA Binding, and Integrative Recombination

Abstract: The integration host factor of Mycobacterium tuberculosis (mIHF) consists of a single polypeptide chain, the product of the ihf gene. We previously revealed that mIHF is a novel member of a new class of nucleoid-associated proteins that have important roles in DNA damage response, nucleoid compaction, and integrative recombination. The mIHF contains a region of 86 amino acids at its N terminus, absent from both ␣-and ␤-subunits of Escherichia coli IHF. However, the functional significance of an extra 86-amino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…S1C,E). Some reports suggested that (Sharadamma et al, 2015(Sharadamma et al, , 2017, in contrast to M. smegmatis IHF (msIHF), M. tuberculosis (mtIHF) includes an additional N-terminal domain (85 amino acids); recently, however, this hypothesis was rejected based on the finding that the longer mihf gene sequence arose from an incorrect annotation of the transcription start (Mishra et al, 2013;Odermatt et al, 2018). Moreover, we confirmed expression of the shorter version of mtIHF by Western blotting comparing lysates from M. smegmatis strains producing either mtIHF-EGFP or msIHF-EGFP fusion proteins (expressed under native promoters; Supplementary Figure S1D).…”
Section: Results Msihf Colocalizes With the Chromosomal Marker Hupb T...mentioning
confidence: 99%
“…S1C,E). Some reports suggested that (Sharadamma et al, 2015(Sharadamma et al, , 2017, in contrast to M. smegmatis IHF (msIHF), M. tuberculosis (mtIHF) includes an additional N-terminal domain (85 amino acids); recently, however, this hypothesis was rejected based on the finding that the longer mihf gene sequence arose from an incorrect annotation of the transcription start (Mishra et al, 2013;Odermatt et al, 2018). Moreover, we confirmed expression of the shorter version of mtIHF by Western blotting comparing lysates from M. smegmatis strains producing either mtIHF-EGFP or msIHF-EGFP fusion proteins (expressed under native promoters; Supplementary Figure S1D).…”
Section: Results Msihf Colocalizes With the Chromosomal Marker Hupb T...mentioning
confidence: 99%